2018
DOI: 10.1007/s41783-018-0031-8
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Adhesion Characteristics of Current and Next Generation Steel Packaging Materials

Abstract: Steel packaging remains an important mean by which foodstuffs and other products can be stored safely for a prolonged period of time. The industry is being challenged by the dual legislative pressures which require the elimination of Chrome (VI) from the manufacturing process and the elimination of bisphenol A as a component from the lacquer system. Initial indications suggest lower adhesive performance, and it has been postulated that thermal treatment may be a mean of improving adhesion. Three substrates (tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The effect of citric acid, demonstrated in Figure 7, is more pronounced on 294269M than the ECCS, and this attributed to the higher chromium level which is applied which allows greater conversion to chromium oxide and thus an increased number of lacquer bonding sites. 33 This mechanism also results in higher substrate/lacquer adhe- may be associated with the corrosion of the substrate surface. The increase in failure force is initially rapid and, in most instances, reached 90% of its final value within 50 hours.…”
Section: Citric Acid Effectmentioning
confidence: 99%
“…The effect of citric acid, demonstrated in Figure 7, is more pronounced on 294269M than the ECCS, and this attributed to the higher chromium level which is applied which allows greater conversion to chromium oxide and thus an increased number of lacquer bonding sites. 33 This mechanism also results in higher substrate/lacquer adhe- may be associated with the corrosion of the substrate surface. The increase in failure force is initially rapid and, in most instances, reached 90% of its final value within 50 hours.…”
Section: Citric Acid Effectmentioning
confidence: 99%
“…This adhesion measurement method provides a physical stress on the surface which is akin to that produced during can forming which can be a primary source of can defects and provides a single nonsubjective numerical value for adhesion. It has been validated in other studies and was repeated for five samples, and repeated measurements were shown to be +/− 0.25 g in terms of adhesion force …”
Section: Methodsmentioning
confidence: 88%
“…Any passivation technology which replaces Cr (VI) will need to prevent the growth of oxide with performance at least comparable with the incumbent Cr (VI). Thermal history and prolonged storage have been shown to be contributory factors to tin oxide growth, and this imposes additional requirements on passivation. The dataset provided by this paper provides a measure against which the future passivation technologies can be compared in terms of the adhesion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High concentrations of Cr (VI) have been found in US tap water, which may be resultant from the discharge of steel, pulp, metal-plating, and leather-tanning facilities, as well as through erosion of soil and rock [ 23 , 24 , 25 ]. REACH (Registration, Evaluation, Authorization and Restriction of Chemicals) legislation require the withdrawal of the use of chromium (VI) compounds due to safety concerns [ 18 ], which requires the steel packaging industry to develop new substrate variants [ 20 ]. One of the most recent developments in this area is Trivalent Chromium Coating Technology (TCCT), which is based on a chromium (III) process [ 6 , 26 ].…”
Section: Introductionmentioning
confidence: 99%